2017
DOI: 10.1371/journal.pone.0185095
|View full text |Cite
|
Sign up to set email alerts
|

Body habitus in patients with and without bronchiectasis and non-tuberculous mycobacteria

Abstract: BackgroundFemale gender, tall stature, presence of bronchiectasis are associated with pulmonary nontuberculous mycobacterial (NTM) infections. The biologic relationship between the body habitus and NTM infection is not well defined and the body habitus profile of the patients with NTM and concurrent bronchiectasis is completely unknown.MethodsWe conducted a case control study at the Miami VA Healthcare System and the University of Illinois Medical Center on patients with pulmonary NTM infections between 2010 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…[ 8 ] Several studies have also consistently shown that in otherwise healthy subjects, low BMI and the female sex were risk factors of NTM-LD. [ 7 , 8 ] While BMI is the most commonly used parameter to characterize body morphotype, BMI can neither distinguish nor quantify muscle mass and fat mass. [ 15 ] To overcome this limitation, the BIA method was used in the current study, which can estimate the exact component of body compositions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 8 ] Several studies have also consistently shown that in otherwise healthy subjects, low BMI and the female sex were risk factors of NTM-LD. [ 7 , 8 ] While BMI is the most commonly used parameter to characterize body morphotype, BMI can neither distinguish nor quantify muscle mass and fat mass. [ 15 ] To overcome this limitation, the BIA method was used in the current study, which can estimate the exact component of body compositions.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 , 6 ] Particularly, female patients, tall statured patients, and patients with low body weights are more susceptible to NTM-LD. [ 7 ] Recent studies demonstrated that the susceptibility of a patient with a thin body to NTM-LD is related to dysregulation of hormones produced by fat tissue. [ 8 , 9 ] Notably, alterations in adipokine levels, implicated in the regulation of immune responses, have been noted to influence the susceptibility to NTM-LD.…”
Section: Introductionmentioning
confidence: 99%
“…Nodular-related bronchiectasis is of signi cance in the diagnosis and treatment of pulmonary NTM infection. Although bronchiectasis has been observed in 20%-30% of patients with NTM, NTM infection seems not common in patients with bronchiectasis [10,27]. Indeed, 34%-50% of patients with multiple small nodules (and sometimes cavity or cavities) combined with their diffusion (or widespread) indicate the presence of active pulmonary NTM infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have indicated that using ICD codes to determine infections from NTM can also miss from 25 to 75% of cases ( 21 ). Recently, authors looked at the accuracy of ICD codes for pulmonary NTM in the VA system, and calculated an accuracy rate as low as 65% ( 36 ). This may indicate an underestimation of true NTM cases, but the change over time may still represent an increase in NTM prevalence.…”
Section: Discussionmentioning
confidence: 99%